Growing together: exploring the politics of knowing and conserving (bio) diversity in a small conservancy in Cape Town - Olwage, Elsemi (Social Anthropology, 2015)
This dissertation is based on research conducted at a small state-managed conservancy called the Edith Stephens Nature Reserve (ESNR) situated in the low-lying flatlands of the Cape Town metropolis. By tracing some of the complex and varied ways in which different ways of knowing and valuing urban "natures" and practices of conservation co-constitute each other, this dissertation critically engages with the social power relations at work in the continual making and unmaking of Cape Town's "natural" heritages. In doing so, I argue for recognizing the ways in which Cape Town's urban "natures" remain entangled with the epistemological, ecological and spatial legacies of colonialism and apartheid. Moreover, by focusing on the ESNR, I explore the current material and discursive practices by the state in relation to urban "nature" conservation. In recent years, the discursive framework of biodiversity conservation was mapped onto ESNR through the state apparatus. At the same time, ESNR was identified as pilot site for an experimental partnership project that was called Cape Flats Nature (CFN), a project that ran from 2002 till 2010 which explored what biodiversity conservation would mean within marginalized, poverty-stricken and highly unequal urban landscapes. By engaging with ESNR's historically constituted material- discursivity, this dissertation argues that, during this time, a particular relational knowledge emerged which, in turn, co-crafted and configured the emerging poetics, politics and practices at ESNR. In doing so, I foreground my main argument - that urban "nature"conservation, far from only being about conserving and caring for nonhuman life worlds, is rather simultaneously about conserving a particular relation to the world, to others and to oneself.